Students' Cognitive Ability Improvement on Mechanical Wave Material with Chamilo Learning Media - I Made Astra; Hilmi Khoirulloh; I Gede Indra Aryasa (Postgraduate, University of Mataram, 2025)
The results of initial observations indicate that students' understanding of the concept of mechanical waves in the Basic Physics course still needs to be improved. The method used in this research is lesson study method with stages, namely plan, see, and do and also a single descriptive research with cognitive ability instrument to improve the quality of learning. The results of the normality test show a pre-test significance value of 0.07 and a post-test of 0.08, which indicates that the data is normally distributed. The paired t-test shows a significance value of 0.00 (p < 0.05), which means that there is a significant difference between the pre-test and post-test results. Meanwhile, the results obtained in this study are that there is an increase in students' cognitive ability with an N-gain result of 0.46 which is included in the moderate criteria (0.30 - 0.70). Therefore, it can be concluded that students' cognitive ability in learning mechanical waves increase after using Chamilo learning media.